If it's not what You are looking for type in the equation solver your own equation and let us solve it.
26+4x=-6x-8(5+7x)
We move all terms to the left:
26+4x-(-6x-8(5+7x))=0
We add all the numbers together, and all the variables
4x-(-6x-8(7x+5))+26=0
We calculate terms in parentheses: -(-6x-8(7x+5)), so:We get rid of parentheses
-6x-8(7x+5)
We multiply parentheses
-6x-56x-40
We add all the numbers together, and all the variables
-62x-40
Back to the equation:
-(-62x-40)
4x+62x+40+26=0
We add all the numbers together, and all the variables
66x+66=0
We move all terms containing x to the left, all other terms to the right
66x=-66
x=-66/66
x=-1
| -2x+6-5x=-71 | | y=5^2-60 | | 11=|3x+5| | | |p-9|=7 | | 6-7x=9-4x-2 | | 9-(x+8)-2x=3+7 | | 4.7x=1.2x+7 | | 3.5x=1.5x+20 | | 3(3y+4)=5 | | 5(45+5)=(z) | | 6-6(x+3)+5x=7+6 | | n/0.2=0.06/2 | | -18x-18x+47x=13-13 | | x^2+15x-694=0 | | 3w2=2w-16=0 | | -3/7x=42 | | 50=13x | | 2(a+3)=4-3(4+8) | | -11x-13=5 | | 4(x+3)-4=7x+2 | | 2x/3+3=9 | | -7(a+2)-4=24-a | | 3m(3+8)=m | | -14x-18=15 | | 6(u-3)=-7u+34 | | 9x-6=10x-10 | | 8c=$60.00 | | 8x-1=4x+1 | | 4(4x-9)=2(8x+6) | | 18=2x-7 | | n/0.4=0.08/5 | | 5/8c=145 |